Evidence for trypanocidal drug resistance at Ferkessedougou feedlot, northern Cote d'Ivoire - Atse, P.A.; Coulibaly, L.; Hecker, P.A.; Krebs, H.A.; D'Ieteren, G.D.M.; Rowlands, G.J.; Leak, S.G.A.; Nagda, S.M. (OAU/ISCTRC, 1995)
Eleven groups of male cattle (39 on average per group) were monitored for presence of trypanosomes at 3-weekly intervals for periods of up to 27 weeks at a feedlot of Ferkessedougou, northern Cote d'Ivoire, in an area supposedly free of tsetse. All animals originated from or grazed during transhumance in south west Mali. The groups were assigned to different treatment regimes as they enter the feed lot. All animals of six groups were treated with diminazene aceturate on the first day of sampling, three groups at a dose of 3.5 mg/kg and three groups at 7 mg/kg body weight. Similarly three groups were treated with isometamidium chloride at a dose of 0.5 mg/kg. As the feed lot ceased its operations, only one group was treated with the same drug at a dose of 1 mg/kg and an 11th group was treated with homidium bromide at a dose of 1 mg/kg. Every animal was thus treated with either diminazene aceturate, isometamidum chloride or homidium bromide at the time of first sampling and with a "sanative pair" if detected parasitaemic again. No animals were detected parasitaemic at any time in the one group initially treated with homidium. Five animals were detected parasitaemic at week 0 in two groups treated with isometamidium chloride at 1 mg/kg bodyweight. Two of these animals were detected parasitaemic again, one at 3 weeks and one at 12 weeks following treatment. Infections were then treated with dimianzene aceturate at 7 mg/kg body weight and apparently cured. No animals were detected parasitaemic at any time in the other two groups treated with isometamidium chloride diminazene aceturate at 3.5 mg/kg, and in 2 of the 22 animals detected parasitaemic 3 and receiving diminazene aceturate at 7 mg/kg body weight. There was 15 subsequent cases of parasitaemia in animals first treated with diminazene aceturate at 3.5 mg/kg body weight that were sampled on at least three occasions following further treatment with isometamidum chloride. Parasitaemia was detected again in 8 animals (53 percent) within 9 weeks of treatment. These results provide evidence of a problem of drug resistance to isometamidum having developed among trypanosomes in two of the eleven groups of animals. Diminazene aceturate at 3.5 mg/kg body weight had apparently failed to cure infections in 14 animals in these two groups. there was however less evidence of drug failure when the higher dose of 7 mg/kg body weight was used in two other groups.